FRONT END LEARNING MANAGEMENT SYSTEM DEVELOPMENT USING THE NEXTJS FRAMEWORK - Baehaqi, Ahmad; Basit, Muhamad Subhi; Indrajit, Richardus Eko; Kurniawan, Rido Dwi (Jurnal Teknik Informatika (Jutif), 2023)
Learning media is currently widely used in the teaching and learning process. Technology and information are two things that cannot be separated from one another in the ever-evolving digital era. Likewise with the education sector which underwent a significant transformation. The Learning Management System is a software application for online learning that supports delivering material online, discussing with students, and controlling student performance. This technological advancement has made many tertiary institutions use web application-based information technology. The current problem is the lack of complete features and less interactive functions to support the Learning Management System. In addition, when the user wants to be more interactive in learning, the Learning Management System generally has a separate feature, which requires the user to switch platforms to use the feature. The development of this Learning Management System is expected to become a more interactive learning platform and have complete features compared to other systems. System analysis is done by describing a system as a whole into its component parts. This is intended to identify and evaluate problems that will later find weaknesses and strengths in the system. The method used in this study is the waterfall starting from making the design of the system to implementing the system that runs in a production environment. The results of this study have several features needed for in-person and online learning which generally do not exist in other Learning Management Systems such as video conferencing, docs & files, group chats, automatic check-ins.